2008
DOI: 10.3341/kjo.2008.22.3.147
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctivolimbal Autograft Using a Fibrin Adhesive in Pterygium Surgery

Abstract: PurposeTo evaluate the efficacy and safety of fibrin bioadhesive in conjunctivolimbal autograft surgery for primary pterygium.MethodsThirty-six eyes in 34 patients were reviewed with nasal primary pterygium who were treated with pterygium excision with superior conjunctivolimbal transplantation with fibrin bioadhesive. Surgical durations were recorded and the patients were followed up on the first day after surgery and then at 1, 2, 4, 8 and 12 weeks postoperatively. The graft-recipient site attachments were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…19 Most importantly however, the operating time, post-operative symptoms, recurrence, and complication rate of the above-described technique (SGF) in our series appears to be equivalent to conventional suture and glue techniques of a similar follow-up duration. 3,4,6,10 Specifically, the risk of graft retraction as described by Tan 7 appears to be no greater without suturing or fibrin glue as long as meticulous dissection of the subepithelial graft tissue is respected. We postulate that as there is an even tension across the whole of the graft interface and no direct tension on the free graft edges, there is reduced stimulus for subconjunctival scar tissue to form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Most importantly however, the operating time, post-operative symptoms, recurrence, and complication rate of the above-described technique (SGF) in our series appears to be equivalent to conventional suture and glue techniques of a similar follow-up duration. 3,4,6,10 Specifically, the risk of graft retraction as described by Tan 7 appears to be no greater without suturing or fibrin glue as long as meticulous dissection of the subepithelial graft tissue is respected. We postulate that as there is an even tension across the whole of the graft interface and no direct tension on the free graft edges, there is reduced stimulus for subconjunctival scar tissue to form.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports favour the use of fibrin glue [2][3][4][5] above sutures with improved comfort, decreased surgical time, reduced complication and recurrence rates have been reported. Suture-related complications include infection, granuloma formation, and chronic inflammation, 6,7 whereas plasma-derived fibrin glue has the potential risk of prion disease transmission and anaphylaxis in susceptible individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al reported that patient's symptoms disappeared in 23 out of 36 eyes (64%) in one week and all the symptoms gone within two weeks after surgery in all patients. [16] Graft oedema was noticed in 78% of patients at day one, which gradually reduced to 4% at the end of 3 months and with short course of topical steroids oedema fully resolved at the end of 6 months in all patients [ Figure 4a]. A study from Philippines reported that postoperatively some amount of graft oedema was present in all eyes and it gradually subsided overtime.…”
Section: Discussionmentioning
confidence: 98%
“…Relapse rates in pterygium following limbal stem cell or limboconjunctival tissue transplantation vary between 0% and 14.6% (23)(24)(25)(26)(27). Conjunctival autograph relapse rates vary between 0% and 33.3% in the literature (11-14, 28, 29).…”
Section: Ayala Et Al (11) Used Bioadhesives In Conjunctival Autographsmentioning
confidence: 99%